The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1309/ajcpemvxes72duif
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of CD5-Positive Nodal Marginal Zone Lymphoma

Abstract: CD5 expression in NMZL correlates with a higher frequency of dissemination, but patients have an indolent clinical course and excellent overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In contrast to the higher rates of nodal MZBCLs expressing CD5 (8.6%), 22 less than 1% of MALT lymphomas are positive for CD5. 23 Splenic MZBCLs exhibit positive CD5 expression in about 20% of the cases.…”
Section: 21mentioning
confidence: 70%
“…In contrast to the higher rates of nodal MZBCLs expressing CD5 (8.6%), 22 less than 1% of MALT lymphomas are positive for CD5. 23 Splenic MZBCLs exhibit positive CD5 expression in about 20% of the cases.…”
Section: 21mentioning
confidence: 70%
“…17,18 However, expression of CD5 also has been detected occasionally in other B-cell lymphomas including extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue, nodal marginal zone lymphoma, splenic marginal zone lymphoma, lymphoplasmacytic lymphoma, follicular lymphoma, and diffuse large B-cell CD5+ follicular lymphoma lymphoma. 9,[19][20][21][22][23] In follicular lymphoma, CD5 expression has been associated with younger age, male predominance and grade 3 morphology. 4,6,8 More recently, Miyoshi et al 10 in Japan reported a series of 22 cases of CD5+ follicular lymphoma and found that patients with CD5+ follicular lymphoma showed a higher frequency of peripheral blood involvement, CD25 and MUM1 expression, and a lower frequency of t(14;18)(q32;q21; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CD23, which is is usually negative, may be actually present in about one third of cases [6]; this occurrence is very important because, if not properly recognized, may lead to diagnostic mistakes. In addition, CD5 expression may be seen roughly in 20% of NMZL; beside this possibility, it has been proven that CD5-positive NMZL display a more disseminated disease, although this occurrence does not impact on prognosis [6,23]. Cyclin D1 must be absent [6].…”
Section: Nmzl May Contain a Variable Amount Of Cells That Range From mentioning
confidence: 99%